Leucine-Rich Repeats and Transmembrane Domain 2 Controls Protein Sorting in the Striatal Projection System and Its Deficiency Causes Disturbances in Motor Responses and Monoamine Dynamics - Ichise, Misato; Sakoori, Kazuto; Katayama, Kei-ichi; Morimura, Naoko; Yamada, Kazuyuki; Ozawa, Hiroki; Matsunaga, Hayato; Hatayama, Minoru; Aruga, Jun (Frontiers in Molecular Neuroscience, 2022)
The striatum is involved in action selection, and its disturbance can cause movement disorders. Here, we show that leucine-rich repeats and transmembrane domain 2 (Lrtm2) controls protein sorting in striatal projection systems, and its deficiency causes disturbances in monoamine dynamics and behavior. The Lrtm2 protein was broadly detected in the brain, but it was enhanced in the olfactory bulb and dorsal striatum. Immunostaining revealed a strong signal in striatal projection output, including GABAergic presynaptic boutons of the SNr. In subcellular fractionation, Lrtm2 was abundantly recovered in the synaptic plasma membrane fraction, synaptic vesicle fraction, and microsome fraction. Lrtm2-KO mice exhibited altered motor responses in both voluntary explorations and forced exercise. Dopamine metabolite content was decreased in the dorsal striatum and hypothalamus, and serotonin turnover increased in the dorsal striatum. The prefrontal cortex showed age-dependent changes in dopamine metabolites. The distribution of glutamate decarboxylase 67 (GAD67) protein and gamma-aminobutyric acid receptor type B receptor 1 (GABABR1) protein was altered in the dorsal striatum. In cultured neurons, wild-type Lrtm2 protein enhanced axon trafficking of GAD67-GFP and GABABR1-GFP whereas such activity was defective in sorting signal-abolished Lrtm2 mutant proteins. The topical expression of hemagglutinin-epitope-tag (HA)-Lrtm2 and a protein sorting signal abolished HA-Lrtm2 mutant differentially affected GABABR1 protein distribution in the dorsal striatum. These results suggest that Lrtm2 is an essential component of striatal projection neurons, contributing to a better understanding of striatal pathophysiology.